Cyclopropanation of (E)-Dehydroaspartic Acid Esters with Furan Derivatives: The Synthesis of Highly Functionalized α-2,3-Methanoamino Acid Esters - Manabe, Atsushi; Matsumoto, Ryotaro; Shinada, Tetsuro (Synlett, 2015)
Highly functionalized α-2,3-methanoamino acid esters were prepared by the cyclopropanation of dehydroaspartic acid esters with 2-methoxyfuran or 2-siloxyfuran derivatives. These reactions proceed smoothly in the absence of any catalysts, bases, additives, or solvents.
Keywords: cyclopropanation; α-2,3-methanoamino acids; furans; dehydroaspartic acid ester